Preserving Tradition, Embracing Innovation Mohsen Foroughi's Maison de'lIran - Ghazaleh Tarkalam (Athens Journal of Business & Economics)
Iranian architecture has left its mark on world history, with its influence reaching the farthest corners of Europe through the creation of Byzantine architecture. The traditional architecture of Iran, as described by Professor Pirnia, is built upon five principles. These principles highlight the evolution of Iranian civilization over time. Mohsen Foroughi, an exemplary Iranian architect, has skillfully merged the essence of Iranian architecture with contemporary ideals, exemplified by his masterpiece, the "Maison de l’Iran" in Paris, designed in a modern style. In this study, we aimed to explore how Foroughi incorporated these five principles of Iranian architecture into his project in France. Employing a descriptive and analytical method, we assessed the physical and structural components of Iranian architecture, examining how Foroughi's work aligns with the principles and values of Iranian architecture. Our findings demonstrate that Foroughi is in line with traditional Iranian architectural values, contextual materials, and climate-friendly design in his works. Furthermore, Foroughi's expertise in Statics, Material Studies, and Structural techniques sciences enabled him to successfully execute large-scale projects. The Maison de l’Iran exemplifies his understanding of modern styles while honoring the principles of Iranian architecture. His work has been instrumental in shaping modern Iranian architecture, reflecting his artistic creativity and inspiration from Iran's architectural heritage.